Peran Dinas Kesehatan Dalam Koordinasi Dan Pembangunan Penyediaan Air Minum Sanitasi Berbasis Masyarakat - Rusnaini, Sasmita; Zulkifli, Zulkifli; Darmawanto, Darmawanto; Poiran, Poiran; Elsyra, Nova; Hamirul, Hamirul (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2022)
The problem of clean water today is a concern in all regions including the Bungo Regency and this study aims to determine the role of the Health Office in the development of community-based water supply and sanitation. By using a descriptive method of qualitative approach and data collection techniques by interviewing informants as many as 17 people. With the results of the study of the Role of the Bungo District Health Office in the Regency of Bungo in evaluating the sources of community-based drinking water supply and the construction of Pamsimas. In accordance with the regulations and main tasks. There are still many community-based sources of drinking water whose quality is beyond the supervision of the Bungo District Health Office. In carrying out the implementation of supervising community-based drinking water supply the Bungo District Health Office is less than optimal, there are barriers such as inadequate human resources, with a less than optimal number of officers, facilities and infrastructure that have not supported good service. Obstacles faced by the Bungo District Health Office, there have been several attempts to overcome constraints, some of which have been carried out such as: Health Office, Applying to Bungo District Regent. In order to issue a circular letter to Rio and Lurah. Stopping Open Defecation is signed by Minister of Health, Governor and Regent, Public Works Agency, proposing additional personnel and proposing additional budget funds